Optimization Of Sludge Settleability And Dewaterability Using Pilot Scale Liquid State Bioconversion Process Under Non-Controlled Conditions - Barghash, Hind F. A. (2008)

(untitled)
The study of microbial treatment of domestic wastewater treatment plant (DWTP) sludge, by liquid state bioconversion (LSB) process, was conducted using several approaches under sterilized controlled conditions in a bench scale with co-substrate supplementation. For this purpose, the mixed strains (P/A) of two selected filamentous fungi SCahmA103 (Aspergillus niger) and WWZP1003 (Penicillium corylophilum) were used to evaluate the performance of the LSB process in the bench scale and pilot scale, under optimized non-controlled conditions without cosubstrate in terms of biodegradation, bioseparation, biosolid accumulations, settling and dewatering of the DWTP sludge. Three numerical parameters, namely sludge concentrations TSS (w/w %), inoculum sizes (v/w %) and inoculum feeding intervals (hrs.), with three levels statistical design under the response surface methodology (RSM), were optimized with and without co-substrate supplementation to evaluate the performance of the process in terms of acclimatization and biodegradation of the DWTP sludge, under non controlled (natural) conditions. The optimum process parameters of the TSS (w/w